Neuronauka poznawcza z punktu widzenia Mocnego Programu Socjologii Wiedzy Naukowej - Marek Więcław (Studia Philosophica Wratislaviensia)
This article aims to apply the main theses of the finitist account of knowledge of the Strong Programme of the Sociology of Scientific Knowledge (SPSSK) to cognitive neuroscience, understood as a methodologically advanced, transdisciplinary research enterprise belonging to the tradition of natural sciences. The text reconstructs the argumentative line of the Strong Programme’s finitism, pointing to its theoretical sources: the late Wittgensteinian semantic concepts together with his rule-following considerations and the network concept of language proposed by Mary Hesse. The application of the conceptual grid of the Strong Programme to contemporary neurocognitive sciences suggests that the natural science scientific and research enterprise on the neurophysiological substrate of cognition is a collective, institutionalised thought process that can be described as a social practice of concept (kind terms) application. This social process of using concepts proceeds in accordance with the concept of meaning- and rule-finitism. Grounded in this concept, the normativity of reference is explained based on the community thesis. If the finitist approach to meaning and knowledge proposed by the Edinburgh School is correct, two conclusions follow. The first directly follows from the formulation of the theses of classification and knowledge finitism: both the future use of neurocognitive terms and the future implications of neuroscientific beliefs are open-ended. The second is that any potential neurocognitive attempts to establish the neuronal mechanism behind meaning determinism are inevitably conducted in the mode of meaning finitism. Consequently, SPSSK seems to precede, in a logical order, all possible results of neurocognitive research, which turns out, like allnatural sciences, a conceptually open-ended and indeterminate system. In traditional epistemic terms, SPSSK claims that no cognitive neuroscientific claim is ever indefeasibly true or false. The crucial conclusion is that any potential neurocognitive attempts to account for the idea of meaning determinism and pinpoint the neuromechanism of semantic closure must themselves be semantically open-ended.